Digital Reading Behavior in Sri Lankan Secondary Education: Cases on Digital Textbook Reading - Prabhashini, Kumesh (University of Colombo, 2022)
The reading behaviour of senior secondary education transformed from print media texts to hypertext with the advent of digital textbooks. According to Mangen's research, shallow reading behaviors like scanning and skimming are prevalent in digital reading, which causes us to read less intently and shallowly. The easiest way to define the idea of "digital textbooks" is as any digital resource used to improve student learning. The purpose of this study was to explore how impact to the digital reading behaviour to the Secondary Education in Sri Lanka. The main objective of the research was how digital reading behaviour impact to the secondary education students’ when using the digital textbooks. This study was driven by a survey methodology and online questionnaire was distributed to 325 senior secondary students in Western Province, Sri Lanka and the raw data from 323 responders was accurate. The questionnaire was created using the "Google doc" and circulated over WhatsApp social media. According to the survey data, Approximately 188 students said they used both digital and traditional textbooks, while 115 said they still used printed textbooks. Only about a quarter of the students prefer to use the digital textbook alone. A smartphone is used by 60.7% of students to access digital textbooks. The use of digital textbooks is founded on the principles of accessibility, portability, and searchability. The exclusion of digital textbooks is due to technological flaws, a desire to read only printed books, Internet vulnerabilities, and the incapacity to read displays. This sample shows that students’ perceptions are influenced by their reading behavior when reading on a digital device.
Keywords: digital reading; reading behaviour; digital textbook; secondary education; Sri Lanka